Influence of Vine Decline Disease on the Amino Acid Metabolism of Watermelon Fruit - Honoka Santo; Shota Tadano; Fumika Inokami; Takuya Nishioka; Takafumi Konaka; Motomu Sakata; Yasufumi Morimoto; Kinya Akashi (Agronomy)
Vine decline (VD) is a recalcitrant syndrome of watermelon, melon, and other cucurbits, often associated with soil-borne pathogens such as Monosporascus cannonballus and characterized by root necrosis, leaf chlorosis, and wilting at the later stage of fruit maturation. The present study examined VD’s effects on watermelon fruits’ metabolism. The VD-affected watermelon fruits had significantly lower lycopene and total solid contents. Still, polyphenols content and total antioxidant activities were comparable with the controls, suggesting that VD inhibited the ripening processes but maintained defensive processes in the fruits. The VD fruits showed a lower calcium level than the controls, while the contents of other major nutrition minerals were not significantly altered. The VD fruits had a lower content of total amino acids, and their composition was characterized by an increase in the percentage fractions for several amino acids, including citrulline, which may reflect the physiological response to the VD-related water deficit condition. The principal component analysis distinguished amino acid profiles between the VD and control fruits, demonstrating that VD significantly influenced their amino acid metabolisms. The present study revealed that VD imposed characteristic impacts on the biochemical behaviors in the watermelon fruits.